Effect of the feeding type on productive performance, carcass characteristics and meat quality of black creole pig of Cajamarca - Paredes Arana, Manuel (2017)
The aim of this study was to evaluate the effect of two diets on the productive performance, characteristics of the carcass and meat quality of the black creole pig of Cajamarca, Peru. A total of 32 weaned piglets were distributed in four treatments with four replicates per treatment and two animals per replicate. Half of the pigs were fed with restaurant waste and poultry slaughterhouse waste and the other half with concentrate based on corn and soy. Half of each group were castrated males and the other half were females. Body weight of pigs was recorded. All animals were slaughtered at 120 days of fattening, determining carcass characteristics and meat quality through the Longissimus lumbar muscle. A significant interaction between feed x sex was found for body weight and feed conversion (p<0.05). The weight and performance of the carcass was not influenced by sex or food. Pigs fed with concentrate obtained higher body weight gain, better feed conversion, higher protein and lower content of oleic acid in the meat than pigs fed with restaurant waste and poultry slaughterhouse waste.